STRATEGIC APPROACH TO SUPPLY CHAIN MANAGEMENT IN LOGISTICS - CHIRIMBU, Sebastian; BURDA, Alexandru (Annals of Spiru Haret University. Economic Series, 2016)
According to its mission, the fundamental purpose of logistics is to contribute to the achievement of customer services in terms of efficiency. Company's performance in the supply chain is given by the delivery service. It must be established from the way the company responds to every order received from the customer as a result of implementing a strategy consisting of a series of specific decisions. A higher level of service requires those decisions to permit the firm to meet an optimal service level and a complete customer satisfaction in terms of price, time value of the invoice, goods arrived safely at their destination. The level at which an order is satisfied is a measure of the performance of the supply chain of the company and of the strategy applied by the company for its management.